2012
DOI: 10.1097/qai.0b013e318256f3bc
|View full text |Cite
|
Sign up to set email alerts
|

Monocyte Activation Markers in Cerebrospinal Fluid Associated With Impaired Neurocognitive Testing in Advanced HIV Infection

Abstract: Background Activated monocytes/macrophages play a role in severe forms of HIV-associated neurocognitive disorders (HAND), but little is known about mechanisms driving milder forms that are prevalent despite combination antiretroviral therapy (cART). To examine relationships of monocyte activation markers to HAND of varying severity, we compared plasma and CSF biomarker levels to neurocognitive test scores in HIV+ subjects. Methods Plasma and CSF sCD14, CCL2, and IL-6 were measured by ELISA in 67 HIV+ subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
132
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 167 publications
(146 citation statements)
references
References 55 publications
12
132
0
2
Order By: Relevance
“…The CSF CXCL10 levels in our patients were similar to or in some cases higher than those reported previously in the literature for MS patients and were also higher than values seen in normal CSF 15. Although CSF CXCL10 elevation has been reported in other disease states,16, 17, 18 this is the first report to our knowledge that PND patients have elevated CSF CXCL10. CCL2 was also detected in PND patient CSF pretreatment, but levels were comparable to those reported for normal individuals (data not shown).…”
Section: Resultssupporting
confidence: 83%
“…The CSF CXCL10 levels in our patients were similar to or in some cases higher than those reported previously in the literature for MS patients and were also higher than values seen in normal CSF 15. Although CSF CXCL10 elevation has been reported in other disease states,16, 17, 18 this is the first report to our knowledge that PND patients have elevated CSF CXCL10. CCL2 was also detected in PND patient CSF pretreatment, but levels were comparable to those reported for normal individuals (data not shown).…”
Section: Resultssupporting
confidence: 83%
“…We have identified IFN-γ as a candidate cellular factor that decreases astrocyte HO-1 expression, which could thus be responsible for the HO-1 deficiency observed in the prefrontal cortex and striatum of HIVinfected individuals. IFN-γ has been shown to be elevated in the CNS of HIV-infected individuals (48,49), even aviremic subjects on suppressive ART (52). We have shown that IFN-γ can reduce the expression of HO-1 in both human astrocytes and noninfected human macrophages, a finding previously described in IFN-γ-treated human glioblastoma cells and human retinal pigment endothelial cells (58,59).…”
Section: Methodssupporting
confidence: 75%
“…These results suggest that the HO-1 deficiency in HIV-infected brain could result from macrophage HO-1 loss induced by HIV replication and astrocyte HO-1 loss induced by IFN-γ signaling. Consistent with this hypothesis, elevated CSF levels of IFN-γ are found in HIV + patients, even those on suppressive ART (52).…”
Section: The Therapeutic Are and Ho-1 Inducer Dmf Attenuates Hiv-mdsupporting
confidence: 55%
“…Elevated plasma concentrations of sCD14 are furthermore associated with increased rates of carotid artery intima-media thickening, a surrogate marker for progression of subclinical atherosclerosis [48]. Interestingly, levels of sCD14 in plasma and CSF are also linked with neurocognitive impairment in advanced HIV-1 infection despite suppressive ART [49,50]. Levels of the soluble scavenger receptor for haemoglobin, CD163, are elevated in both early and chronic infection, and parallel to viral load and associated with monocyte expansion [51].…”
Section: Monocyte and Macrophage Activation In Comorbiditiesmentioning
confidence: 95%